RASIONALITAS CALON KEPALA DESA DI PONOROGO MENGUNJUNGI MAKAM BATORO KATONG MENJELANG PILKADES TAHUN 2019 - Ramadhani, Haqia Alfariz (Paradigma, 2021)
The election of village heads in Java is still closely related to the traditions and beliefs that exist in society. Pilgrimage to the grave is one of the traditions of the Javanese people that exist among prospective village heads. Ahead of the 2019 Pilkades, several candidate of village heads in Ponorogo visited the grave of Batoro Katong. The aim of this study is to analyze the rational action from candidate of village head visited the grave of Batoro Katong before the 2019 Pilkades. The method of this research is qualitative research with the verstenhen approach. The research subjects are candidate of village heads who visited Batoro Katong's grave before the 2 2019 Pilkades. The perspective of Max Weber's rationality theory was used as the analysis knife of this research. The results showed that the candidate of village head visited Batoro Katong's grave ahead of the 2019 Pilkades based on rational values and traditional rational actions. The rational action of the religious values of the candidate for village head is to pray for the dead as a religious suggestion whose law is sunnah. Another rational action based on religious values, the candidate for village head, hopes to receive wasilah, karomah and blessings from qarin.. Rational action values politeness because they want to respect the success team's invitation. Meanwhile, traditional rational action is influenced by the meaning of pilgrimage as a Javanese tradition. The candidate of village head also believes in the supernatural powers possessed by Batoro Katong to grant their wish. Keywords: Cakades, Rationality, Pilgrimage, Grave of Batoro Katong